2012
DOI: 10.1037/a0025618
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Sociocultural Attitudes Towards Appearance Questionnaire-3 in a mixed-gender young-adolescent sample.

Abstract: Thin-ideal (or media) internalization is an important eating disorder risk factor that has become a central target of many prevention programs. However, evidence for its valid assessment in young, mixed-gender, adolescent samples is limited, and the current study is the first published to explore the psychometric properties of the 30-item Sociocultural EXAMINATION OF THE SATAQ-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 70 publications
1
19
0
5
Order By: Relevance
“…Llorente, Warren, Lourdes Pérez de Eulate and Gleaves [49] and Wilksch and Wade [50] recently used this method to examine the equivalence of the factor structure the SATAQ-3 across different groups. Although confirmatory factor analysis is sometimes used in such situations, Lorenzo-Seva and ten Burge [46] noted that “exploratory factor analysis (EFA) might be more appropriate as a basis for factor comparisons than the CFA approach in most applications, especially in large multidimensional solutions that do not approach very simple structures.” Lorenzo-Seva and ten Burge [46] found that values for congruence coefficients ranging from .85–.94 indicate fair similarity and values higher than .95 indicate that two factors can be considered equal.…”
Section: Methodsmentioning
confidence: 99%
“…Llorente, Warren, Lourdes Pérez de Eulate and Gleaves [49] and Wilksch and Wade [50] recently used this method to examine the equivalence of the factor structure the SATAQ-3 across different groups. Although confirmatory factor analysis is sometimes used in such situations, Lorenzo-Seva and ten Burge [46] noted that “exploratory factor analysis (EFA) might be more appropriate as a basis for factor comparisons than the CFA approach in most applications, especially in large multidimensional solutions that do not approach very simple structures.” Lorenzo-Seva and ten Burge [46] found that values for congruence coefficients ranging from .85–.94 indicate fair similarity and values higher than .95 indicate that two factors can be considered equal.…”
Section: Methodsmentioning
confidence: 99%
“…Missing data is an inevitable feature of school based research, particularly in longitudinal designs that extend across school years where as reported in our original trial, almost half of those participants lost to 2.5-year follow-up had changed schools (Wilksch & Wade, 2009a). Second, it has been previously suggested that there is less construct stability in some eating disorder risk factors over time in young-adolescents compared to olderadolescent and young-adult samples (McKnight Investigators, 2003;Wilksch & Wade, 2012). As such, some caution is required in interpreting the current findings until a replication trial is available.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have reported sound psychometric properties for these measures in use with adolescent populations (Banasiak, Wertheim, Koerner, & Voudouris, 2001;Nishizono-Maher, Miyake, & Nakane, 2004;Wilksch & Wade, 2012). These measures are summarized in Table 1, including the number of items, internal reliability from the current study (Cronbach's alpha), scoring range and example item.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In sum, Media Smart is supported by research that suggests that it can be useful for a universal audience that is under the age of 15 who is at both low- and high-risk of developing an ED. That said, replication trials, particularly independent replication trials, in this line of research are needed with young individuals, as it has been suggested that ED risk factor constructs may be less stable in young adolescents, as opposed to older adolescents [67]. …”
Section: Reviewmentioning
confidence: 99%